Influencia de la edad de los veronicélidos en la infección con Angiostrongylus costaricensis - Conejo, Marta E.; Morera, Pedro (Revista de Biología Tropical, 1988)
In Costa Rica, Veronicellid slugs are the most important intermediate hosts for Angiostrongylus costaricensis. Apparently, these molluscs develop a resistant mechanism after being exposed to the infection. In naturally infected slugs, the higher infection rates were found in large slugs, but they usually bear few larvae. Large number of larvae were found in medium sized molluscs. Experimental infection in laboratory breed slugs produced an amebocytic reaction around developing larvae; later, the formation of a fibrotic capsule is observed. When there is a second infection, cell reaction is stronger and the larvae show degenerative signs. This cell-mediated resistant mechanism seems to explain why the biggest molluscs, although more probably exposed to infection, bear fewer larvae.